2021
DOI: 10.24018/ejbio.2021.2.6.301
|View full text |Cite
|
Sign up to set email alerts
|

Latex Harvesting Technologies Adapted to Hevea brasiliensis Muell Clones GT 1; RRIC 100 and BPM 24 Arg. (Euphorbiaceae) belonging to the Moderate Metabolism Class in the Socio-economic Context of Côte d'Ivoire

Abstract: Improving the productivity of rubber trees has always been a major concern for rubber farmers. The majority of growers opt for overexploitation of the trees. This disturbs the physiological balance of the rubber trees, which leads to the recrudescence of tapping panel dryness and rather to a drop in production. To solve this problem, the present study proposes to define a latex harvesting technology (or technologies) for the moderate metabolism clone class that will allow the improvement of plantation yield an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This result confirms that treatment T1 is more productive for these clones. This assertion is confirmed by the results of Diarrassouba et al, [11] who obtained an average dry rubber yield of 50 g/t/t in For clone RRIC 100, both types of tapping induced statistically identical average dry rubber yields. This result attests that both types of tapping are productive for this clone and that treatment T1 does not influence the yield of this clone.…”
Section: Effect Of the Types Of Tapping On Dry Rubber Yieldsupporting
confidence: 78%
“…This result confirms that treatment T1 is more productive for these clones. This assertion is confirmed by the results of Diarrassouba et al, [11] who obtained an average dry rubber yield of 50 g/t/t in For clone RRIC 100, both types of tapping induced statistically identical average dry rubber yields. This result attests that both types of tapping are productive for this clone and that treatment T1 does not influence the yield of this clone.…”
Section: Effect Of the Types Of Tapping On Dry Rubber Yieldsupporting
confidence: 78%
“…Although some studies showed that quick starter clones have a low response to ethylene stimulation and consequently are less suitable to the low-frequency tapping (Atsin et al 2014;Atsin et al 2017), some new quick-starter clones may be more responsive to ethylene application. On the other hand, several studies showed that high sugar loading clones were able to amplify the benefit of low-frequency tapping (Gohet et al 1996;Soumahin et al 2009;Lacote et al 2010;Diarrassouba et al 2012). High sugar-loading clones are also more resistant to TPD due to the abundant availability of latex and antioxidant material Gohet et al 1997Gohet et al , 2019.…”
Section: Limited Use Of Latex Diagnosis In Breeding Programmentioning
confidence: 99%